2019
DOI: 10.1007/s40266-019-00637-0
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Antimicrobial Stewardship for Older People in Care Homes: A Systematic Review

Abstract: Compliance with ethical standards As this was a systematic review, ethical approval to conduct the study was not required. Conflicts of interest Hoa Nguyen, Michael Tunney and Carmel Hughes have no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Nevertheless, it is very difficult to determine the original source of transmission in this population. The crucial role of care homes in the transmission of MDRO infections has been consistently reported [13][14][15][16]. A number of factors could explain this high transmission, e.g., healthcare personnel simultaneously working in several care homes, the high rate of hospitalization and antibiotic use in this vulnerable population, or a lack of resources and training in infection prevention measures, as previously suggested in Spain [17].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Nevertheless, it is very difficult to determine the original source of transmission in this population. The crucial role of care homes in the transmission of MDRO infections has been consistently reported [13][14][15][16]. A number of factors could explain this high transmission, e.g., healthcare personnel simultaneously working in several care homes, the high rate of hospitalization and antibiotic use in this vulnerable population, or a lack of resources and training in infection prevention measures, as previously suggested in Spain [17].…”
Section: Discussionmentioning
confidence: 75%
“…Although the daily probability of microbial transmission in nursing homes is significantly lower than in hospitals, the transmission of MDRO may be more effective given the increased length of stay of residents. A recent systematic review found a high frequency of AMDR in care homes [14]. In Spain, the transmission of methicillin-resistant Staphylococcus aureus (MRSA) and a high rate of quinolone-resistant MRSA have been reported in community care homes [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This does raise the issue of the most appropriate outcome to be used in a future, larger definitive trial. A systematic review 89 has extracted the range of outcomes that have been used in RCTs that have focused on antimicrobial stewardship in care homes for older people, which are shown in Table 32.…”
Section: Data Collection From Various Sourcesmentioning
confidence: 99%
“…There are two Cochrane Systematic Reviews on interventions to improve antibiotic prescribing; one is in the ambulatory care setting [14] and the other is among hospital inpatients [15] . The ambulatory care review has not been updated since 2005 but more recent systematic reviews have been published about interventions in primary care, especially for respiratory diseases [13,16,17] and care homes [18] . They focused speci cally on primary care institutions and physicians, or systematic reviews of educational interventions.…”
Section: Introductionmentioning
confidence: 99%